The Community Land Act in Kenya Opportunities and Challenges for Communities - Liz Alden Wily (Land, 2018)
Kenya is the most recent African state to acknowledge customary tenure as producing lawful property rights, not merely rights of occupation and use on government or public lands. This paper researches this new legal environment. This promises land security for 6 to 10 million Kenyans, most of who are members of pastoral or other poorer rural communities. Analysis is prefaced with substantial background on legal trends continentally, but the focus is on Kenya’s Community Land Act, 2016, as the framework through which customary holdings are to be identified and registered. A main conclusion is that while Kenya’s law is positive and even cutting-edge in respects, legal loopholes place communities at risk of their lands not being as secure as promised ahead of formalization, and at risk of losing some of their most valuable lands during the formalization process. This is mainly due to overlapping claims by the national and local government authorities. Political will to apply the law is also weak. The truism that the law is never enough on its own to secure social change is illustrated. With or without legal protection, the assistance of non-state actors will be needed to help communities secure their lands under formal collective entitlements. The need for judicial interpretation of disputed legal provisions may also be required to ensure new constitutional principles are delivered.